Association schemes arising from bent functions - Pott, Alexander (2012)
We give a construction of 3-class and 4-class association schemes from s-nonlinear and differentially 2s-uniform functions, and a construction of p-class association schemes from weakly regular p-ary bent functions, where p is an odd prime.